2023
DOI: 10.1371/journal.pone.0279616
|View full text |Cite
|
Sign up to set email alerts
|

Wheat ergot fungus-derived and modified drug for inhibition of intracranial aneurysm rupture due to dysfunction of TLR-4 receptor in Alzheimer’s disease

Abstract: Background Alzheimer’s disease (AD) is a form of dementia that strikes elderly people more frequently than it does younger people. The cognitive skills and memory of Alzheimer’s sufferers continue to deteriorate over time. Recent studies have shown that patients with AD have greater amounts of inflammatory markers in their bodies, which suggests that inflammation occurs early on in the progression of the disease. There is a possibility that Aß oligomers and fibrils can be recognised by TLRs, in addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The Sandip et al. reported that 2-Bromoergocryptine Mesylate is a potential candidate drug to prevent IA rupture by targeting TLR4 receptor ( 129 ). However, as a special agent for targeting TLR4 protein active region in diabetes and Alzheimer’s disease inflammation, 2-Bromoergocryptine Mesylate still has obstacles in broadening pharmacological effects for the IA.…”
Section: Macrophages Relevant Signaling Pathways and Therapy Strategi...mentioning
confidence: 99%
“…The Sandip et al. reported that 2-Bromoergocryptine Mesylate is a potential candidate drug to prevent IA rupture by targeting TLR4 receptor ( 129 ). However, as a special agent for targeting TLR4 protein active region in diabetes and Alzheimer’s disease inflammation, 2-Bromoergocryptine Mesylate still has obstacles in broadening pharmacological effects for the IA.…”
Section: Macrophages Relevant Signaling Pathways and Therapy Strategi...mentioning
confidence: 99%
“…Furthermore, bee venom is an effective antimicrobial [13], anti-inflammatory, anti-apoptosis, anti-fibrosis, and anti-atherosclerosis agent [14,15], as well as an antibacterial agent against a variety of Gram-positive/negative bacteria strains [16][17][18]. Using bee product combinations instead of conventional medication, according to Zambrano et al [19] and Tanu gur and Kekeço glu [20], may have beneficial results.…”
Section: Introductionmentioning
confidence: 99%